2011
DOI: 10.12659/msm.881893
|View full text |Cite
|
Sign up to set email alerts
|

Review of therapeutic strategies for osteosarcoma, chondrosarcoma, and Ewing’s sarcoma

Abstract: SummaryThe most prevalent forms of bone cancer are osteosarcoma, chondrosarcoma, and Ewing’s sarcoma. Although chemotherapy and radiotherapy have replaced traditional surgical treatments, survival rates have undergone only marginal improvements. Current knowledge of the molecular pathways involved in each type of cancer has led to better approaches in cancer treatment. A number of cell signaling molecules are involved in tumorigenesis, and specific targets have been identified based on these signal transducers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
92
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 140 publications
(174 reference statements)
0
92
0
Order By: Relevance
“…Despite remarkable advances in the combined used of chemotherapy, radiotherapy and surgical ablation of the primary tumor, survival rates have yet to improve over those of the 1970s (3). Approximately 40% to 50% of patients develop metastasis, often pulmonary metastasis, even after curative resection of the primary tumor, and the 5-year survival rate of osteosarcoma patients with metastases is even lower than 30% (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Despite remarkable advances in the combined used of chemotherapy, radiotherapy and surgical ablation of the primary tumor, survival rates have yet to improve over those of the 1970s (3). Approximately 40% to 50% of patients develop metastasis, often pulmonary metastasis, even after curative resection of the primary tumor, and the 5-year survival rate of osteosarcoma patients with metastases is even lower than 30% (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] For example, studies have shown that over-activation of phosphatidylinositol 3-kinase (PI3K)/Akt/mammalian target of rapamycin (mTOR) pathway is an important contributor of progression and chemo-resistance of malignant osteosarcoma. [7][8][9][10][11] PI3K, a heterodimer consisting of the p85 regulatory and p110 catalytic subunits, is a major signaling component downstream of receptor tyrosine kinases (RTKs). 12 PI3K activates its downstream Akt, which phosphorylates several substrates involved in various key cellular processes including cell growth, proliferation, survival, apoptosis-resistance and metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Despite modern treatment protocols that combine chemotherapy, surgery, and sometimes radiotherapy, the 5-year survival rate for patients diagnosed with osteosarcoma remains at 60%~70% since the 1970s. 8 As surgical techniques and implants have evolved, chemotherapeutic agents used today seem to be wholly similar to those used 40 y ago. Moreover, adverse effects associated with chemotherapies, chemoresistance, recurrence, and pulmonary metastasis make clinical management of osteosarcoma face numerous challenges.…”
Section: Introductionmentioning
confidence: 99%